Dramatically Accelerated Formation of Graphite Intercalation Compounds Catalyzed by Sodium. Issue 15 (4th March 2023) - Iyo, Akira; Ogino, Hiraku; Ishida, Shigeyuki; Eisaki, Hiroshi
Abstract: Graphite intercalation compounds (GICs) have a variety of functions due to their rich material variations, and thus, innovative methods for their synthesis are desired for practical applications. It is discovered that Na has a catalytic property that dramatically accelerates the formation of GICs. It is demonstrated that LiC6 n ( n  = 1, 2), KC8, KC12 n ( n  = 2, 3, 4), and NaC x are synthesized simply by mixing alkali metals and graphite powder with Na at room temperature (≈25 °C), and AE C6 (AE  = Ca, Sr, Ba) are synthesized by heating Na‐added reagents at 250 °C only for a few hours. The NaC x, formed by the mixing of C and Na, is understood to act as a reaction intermediate for a catalyst, thereby accelerating the formation of GICs by lowering the activation energy of intercalation. The Na‐catalyzed method, which enables the rapid and mass synthesis of homogeneous GIC samples in a significantly simpler manner than conventional methods, is anticipated to stimulate research and development for GIC applications. Abstract : Pellets of graphite intercalation compounds (GICs) are synthesized by the Na‐catalyzed method. AM –GICs (AM  = Li, Na, K) are formed simply by mixing AM and graphite with Na at room temperature. A Ca‐GIC (CaC6 ) is formed by heating a mixture of Ca, graphite, and Na at 250 °C for only several hours.